Tantangan dan Strategi Komunikasi Lintas Budaya Mahasiswa D3 Bahasa Jepang Selama Magang di Jepang - Astuti, Bekti Setio; Muryati, Sri; Trismanto, Trismanto; Cahyani, Septa Wiki Dwi (KIRYOKU, 2026)
This study aims to identify the challenges and intercultural communication strategies of Indonesian vocational students majoring in Japanese during their internship programs in Japan. Despite possessing intermediate Japanese proficiency at the JLPT N3 level, students often experience difficulties in pragmatic communication and cross-cultural interaction in Japanese workplaces. This research employs a mixed-methods approach. Quantitative data were collected through an online questionnaire distributed to 50 students, with 35 valid responses analyzed using descriptive statistics (frequency and percentage). Qualitative data were obtained from open-ended responses and analyzed using thematic coding.  The results indicate that the main challenges include expressing disagreement, responding to criticism, understanding indirect instructions, and interpreting ambiguous expressions characteristic of Japan’s high-context communication style. To cope with these challenges, students adopt several strategies, such as direct clarification, observation and imitation of local communicative behavior, peer consultation, and selective use of digital translation tools. Furthermore, the internship experience contributes significantly to students’ understanding of Japanese work culture, including values of diligence, punctuality, responsibility, and respect for hierarchy. These findings highlight the importance of pre-departure training that integrates linguistic competence with intercultural communication and pragmatic awareness to better prepare vocational students for professional environments in Japan.